2007
DOI: 10.1007/s11082-008-9186-9
|View full text |Cite
|
Sign up to set email alerts
|

Logic gates based in two- and three-modes nonlinear optical fiber couplers

Abstract: In this paper we did a study of logic gates obtained in the operation of a three-core non linear directional coupler (TNLDC) and an asymmetric two-core coupler (DNLDC) operating in the CW regime (the laser signals have the same wavelength). The symmetric three-core coupler (TNLDC), with their cores identical, in a planar arrangement, was studied using a control pulse applied to the first core. The second structure is an asymmetric twocore coupler (DNLDC). Looking at the transmission characteristics of the devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In tables 2a-2b three possibilities are leading for three different AND gates, in tables 3a-3b two possibilities and in table 1 one possibility. In comparing the logic gates, we will use the figure-of-merit of the logic gates [FOMELG(dB)] defined as a function of the extinction ratio of the gate outputs [3]. We will look for the sum of the module values of the extinction ratio [Xatio (dB)] for each output of the logic gate.…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In tables 2a-2b three possibilities are leading for three different AND gates, in tables 3a-3b two possibilities and in table 1 one possibility. In comparing the logic gates, we will use the figure-of-merit of the logic gates [FOMELG(dB)] defined as a function of the extinction ratio of the gate outputs [3]. We will look for the sum of the module values of the extinction ratio [Xatio (dB)] for each output of the logic gate.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…The performance was studied in view of the possible use of these devices as logic gates in optical networks. To compare the performance of these devices we will use a figure-of-merit of the logic gates (FOMELG) [3].…”
Section: Introductionmentioning
confidence: 99%
“…[14]. On the other hand, in fiber couplers a full set of logic functions including AND, NAND, XOR, NOT and OR gates are numerically demonstrated using two-core and three-core fiber coupler switches operating in the continuous wave regime [3]. Especially, it has been shown that the logic gates AND, OR and XOR can be constructed from an asymmetric two-core fiber coupler and in the symmetrical three core fiber coupler NAND, AND, OR, XOR and NOT logical gates can be realized.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of schemes have been proposed to realize all-optical logic gates such as using dielectric (or metallic) waveguides, [3][4][5] nonlinear effects in optical fibers, [6][7] and semiconductor optical amplifiers. Recently, a number of schemes have been proposed to realize all-optical logic gates such as using dielectric (or metallic) waveguides, [3][4][5] nonlinear effects in optical fibers, [6][7] and semiconductor optical amplifiers.…”
Section: Introductionmentioning
confidence: 99%